Prevalence of hepatitis B and C and relationship to liver damage in HIV infected patients attending Joint Clinical Research Centre Clinic (JCRC), Kampala, Uganda - Baseke, Joy (Afr Health Sci, 2015)
BACKGROUND: Hepatitis B and C viruses cause death due to liver disease worldwide among Human Immunodeficiency Virus (HIV) positive individuals. Hepatitis B (HBV) and HIV have similar routes of transmission primarily; sexual, intravenous injections and prenatal while hepatitis C (HCV) is transmitted mainly through blood transfusion. Human immunodeficiency virus increases the pathological effect of hepatitis viruses and potentiates re-activation of latent hepatitis infections as a result of reduced immunity. The increase in use of antiretroviral (ARVs) drugs has led to longer period for patient survival and apparent increase in liver disease among HIV positive individuals. OBJECTIVE: This study aimed at determining the prevalence of HBV, HCV, their co-infection with HIV and their effect on liver cell function METHOD: This was a cross sectional study conducted at the Joint Clinical Research Centre (JCRC) among HIV positive individuals attending the clinic. Patients were enrolled after obtaining a signed informed consent or assent for children below 17 years. Serum samples were collected for detection of Hepatitis B surface antigen (HBsAg), HCV specific antibodies and alanine aminotransferase (ALT) liver enzyme. RESULTS: Of the 89 patients enrolled, 20 (22.5%) had at least one hepatitis virus, 15 tested positive for HBsAg (16.9%) and 5 for HCV (5.6%), one had both viruses. Hepatitis B was more prevalent among women (13 out of 57, 22.8%) than men, (2 out of 32, 6.2%), while HCV was higher among men (4 out of 32, 12.5%) than women (1 out of 57, 1.8%). Seven of 89 patients (7.9%) had elevated ALT, indicative of liver cell injury. Of these with liver cell injury, one individual tested positive for HBsAg and another one individual tested positive for HCV specific antibodies. CONCLUSION: The prevalence of HBV is high in HIV positive individuals with more women commonly infected. The Prevalence of HCV is lower than that of HBV with more men commonly infected. Co-infection of Hepatitis B and C viruses was uncommon. This study reveals a high prevalence of liver cell injury among HIV positive individuals although the injury due to HBV or HCV infection was lower than that which has been documented. From this study, the high prevalence of HBV and HCV among HIV positive individuals point to a need for screening of HIV positive individuals for the hepatitis viruses.